A Performance Analysis Model for Corporate Human Resource Management Based on Extenics Theory - Mingyan Li; Tiantian Gao; Jianxue Wang; Huanyu Wang (Discrete Dynamics in Nature and Society)
There are several problems with the performance analysis of corporate human resource management (HRM), namely, the incomplete index system and the difficulty in decision-making under multiple fuzzy factors. To solve these problems, this paper improves the method for corporate HRM performance analysis (HRMPA). First, a novel corporate HRMPA index system was established under the principle of comprehensiveness. Next, the fuzzy closeness of corporate HRMPA was calculated based on fuzzy theory, and the extenics correlation coefficient of corporate HRMPA was computed with the aid of the extenics theory. Then, fuzzy extenics factors were introduced to create an integrated corporate HRMPA model. The proposed model was proved valid and feasible through case analysis. The research results shed new light on the theories of HRMPA and enjoy great applicable value in engineering.